[PP.15.10] EUSTAR: EUROPEAN SOCIETY OF HYPERTENSION TELEMEDICINE IN ARTERIAL HYPERTENSION REGISTER - DESIGN AND RATIONALE. (September 2017) - Schulz, E.G.; Neumann, C.L.; Middeke, M.
Abstract : Objective: Failing to reach blood pressure (BP) goals is a major problem in treatment of hypertension, causing a high socioeconomic burden, sequel morbidities and strongly increased mortality. Recent studies demonstrated that interventional decentralized telemonitoring (idTM®) can strongly improve BP management in hypertension including high risk patients. In the EDiMed-Project (efficiency analysis of services in telemedicine) - supported by German Ministry for education and research - the cost-benefit ratio was analyzed and a positive socioeconomic impact was found. Design and method: This project aims at establishing a telemonitoring system that allows to extend this service to all European Excellence centers for hypertension treatment and ultimately to all physicians treating hypertensive patients in Europe. For this effort, the unique software SciTIM® providing highest standard of data security was developed for the register to allow: Making idTM® available to physicians and patients across Europe Establishing telemedical standards for selected hypertensive indications (renal failure, pregnancy, juveniles) Establishing a system for collections of high quality epidemiologic data from daily medical practice, ultimately extend beyond planned register Establishing a digital interface for direct interaction between specialists and general practitioners based on patient data. Figure. No caption available. Results: The register nucleus started with 8 ESH-centers in 2017. To integrate data directly from the data management systems the project has and will generate interfaces to the most commonly used medical data management systems. In addition, the system provides an user interface to physicians, enabling to monitor their patient's telemonitoring progress at the first time directly in their electronic health records enabling physicians to set individual patient limits and specific rules to pro-actively alert staff members via auto generated messages and daily reports. Conclusions: The EUSTAR consortium has establish a register based on needs of medical specialists under the aegis of the ESH and will roll out this register throughout Europe. A database was created that allows safe and standardized exchange of data. The System include interfaces for data collection from medical measurement devices and be open for all possible providers and also for other data than the first two parameters blood pressure and body weight.